MAPA DOS HOMICÍDIOS FEMININOS NAS MESORREGIÕES DE PERNAMBUCO - Maria Eduarda Antonino Vieira (Centro Universitário de Belo Horizonte, 2019)
eoi/doi Deposit-Electronic Object Identifier http://eoi.citefactor.org/10.11248/ehum.v10i2.2154 Map of the Murders of Women in the Mesoregions of Pernambuco - Brasil